A potential use of a hydrophilic polymeric material to enhance durability properties of pavement materials. (1st September 2017) - Georgees, Romel N.; Hassan, Rayya A.; Evans, Robert P.
Highlights: A synthetic polyacrylamide (PAM) has been used to stabilize three types of soils. Strength and durability properties of the treated soils have been assessed. These properties were significantly improved when using PAM additive. PAM is found to be a promising additive to improve soil engineering properties. Abstract: With the increasing demands for stable and high quality materials in road construction, the need for opening new gravel borrow pits is increasing, which compromises the ability of future generations to meet their own needs. Therefore, stabilizing existing or low quality materials to meet the desired performance criteria is needed. Polymer stabilizing additives have been shown to enhance strength and durability characteristics of soils in addition to their advantage of lower carbon footprints compared to traditional stabilizing ones. An extensive laboratory investigation has been carried out to assess the potential use of polymeric stabilization in improving engineering properties of three soil types for use in foundation layers of flexible pavements. A synthetic hydrophilic polyacrylamide-based (PAM) additive has been used to stabilize the soils. The strength characteristics of PAM-treated soils have been assessed by conducting unconfined compressive strength (UCS) tests and their durability characteristics have been evaluated by conducting hydraulic conductivity tests. Erosion and abrasion tests have been also performed to characterize the durability of the treated materials when subjected to traffic abrasion and water erosion. Additionally, microstructure analysis has been performed by conducting Scanning Electron Microscopy (SEM) test. The tests have shown that treating soils with PAM results in significant improvements in their strengths however, those with high content of fines are associated with low UCS values. The tests results have also shown that PAM-treated soils have considerable reductions in their permeability, dramatic improvements in their erosion resistance and significant improvements in abrasion resistance.